2022
DOI: 10.3389/fendo.2022.1044691
|View full text |Cite
|
Sign up to set email alerts
|

T3 levels and thyroid hormone signaling

Abstract: The clinical availability of tissue-specific biomarkers of thyroid hormone (TH) action constitutes a “holy grail” for the field. Scientists have investigated several TH-dependent markers, including the tissue content of triiodothyronine (T3)—the active form of TH. The study of animal models and humans indicates that the T3 content varies among different tissues, mostly due to the presence of low-affinity, high-capacity cytoplasmic T3 binding proteins. Nonetheless, given that T3 levels in the plasma and tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 105 publications
0
12
0
1
Order By: Relevance
“…Interestingly, concomitant T2DM resulted in no further reductions in circulating MOTS-c levels compared to patients with COPD alone; these results suggest that the effects of these two diseases on MOTS-c levels are not additive. Low MOTS-c levels, as happens with “low T3 sick euthyroid syndrome”, may be a generalized non-specific response to many illnesses ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, concomitant T2DM resulted in no further reductions in circulating MOTS-c levels compared to patients with COPD alone; these results suggest that the effects of these two diseases on MOTS-c levels are not additive. Low MOTS-c levels, as happens with “low T3 sick euthyroid syndrome”, may be a generalized non-specific response to many illnesses ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question is justified whether the current reference intervals suffice for persons using L-T4. As mentioned previously, Salas & Bianco ( 38 ) suggested that (F)T3 concentrations may reflect TH status in L-T4 treated people even better than FT4. On the other hand, an analysis of the relationship between psychological well-being and FT4, FT3 and TSH in a large group of patients on L-T4 showed that psychological well-being correlates with FT4 but not with FT3 levels ( 50 ).…”
Section: Pitfalls Of Biochemical Measurements In Primary (Subclinical...mentioning
confidence: 71%
“…This could lead to a mismatch in plasma TH concentrations and symptoms in L-T4 treated patients. In the present article collection on “(Re)defining hypothyroidism: the key to patient-centered treatment”, Salas & Bianco ( 38 ) advocated the use of (free) triiodothyronine ((F)T3) during treatment, as kinetic studies revealed that plasma (F)T3 levels can accurately predict tissue T3 content and T3 signaling in most tissues, except for the brain. Given this direct relationship between plasma and tissue T3 contents and T3 signaling in most tissues, the authors suggest that clinicians managing patients with hypothyroidism should refocus attention on monitoring plasma (F)T3 levels in addition to TSH.…”
Section: Persistent Symptoms In Levothyroxine-treated Patientsmentioning
confidence: 99%
“…FT4 and FT3 enter cells via specific transporters, they bind to cytoplasmic proteins and further enter the nucleus where they bind to thyroid receptors (TRs). The affinity of TR for T3 is approximately 20 times greater than for T4 (Salas‐Lucia & Bianco, 2022). In the nucleus, thyroid hormones affect gene expression but exert some nongenomic effects as well (Davis et al, 2021, 2023).…”
Section: Physiological Importance Of Iodinementioning
confidence: 99%
“…Thyroid hormones in the circulation exist in free, physiologically active form (the so-called free T4 and T3, FT4 and FT3) and are bound to proteins. Less than 1% of total T4 and T3 is found in a free form, while the majority is bound to thyroxine-binding globulin (TBG), transthyretin (TTR), and albumin, which buffer their concentration in blood (Salas-Lucia & Bianco, 2022). The distribution of thyroid hormones between proteins is governed by their affinity for T4/T3 resulting in 75% of hormones bound to TBG, 20% to TTR, and 5% to albumin (Refetoff, 2000).…”
Section: Metabolism Of Iodinementioning
confidence: 99%